Assessment of Energy of Consciousness Healing on Cell Growth of Plant Stem Cells Callus Culture - Nayak Gopal; Kumar Trivedi Mahendra; Branton Alice; Trivedi Dahryn; Jana Snehasis (International Physiology Journal, 2018)
The present study was aimed to evaluate the effect of Consciousness Energy Healing Treatment on plant callus of Mandukparni (Centellaasiatica), Katsarika (Barleriacristata), and Amla (Phyllanthus emblica) in Murashige & Skoog liquid medium (MS) for its growth and yield on day 7. The plant callus of all the three plants were divided into two parts, one part received Biofield Energy Treatment remotely (known as The Trivedi Effect®-Energy of Consciousness Healing Treatment) by a renowned Biofield Energy Healer, Gopal Nayak and denoted as Biofield Energy Treated group, while another part did not receive any treatment and defined as control. Plants callus were observed on day 7 after treatment and visualized under phase contrast microscope for cell growth, captured photomicrographs along with wet weight compared with day 0. Results suggested that three plants viz. Mandukparni, Katsarika, and Amla callus after 7 days showed a significant improved growth rate as compared with the respective untreated groups. The weight of the callus growth (in mg) after Biofield Energy Treatment among Mandukparni, Katsarika, and Amla callus on day 7 was 630, 782, and 920 mg, respectively. However, the percentage increase in weight of the callus in Mandukparni, Katsarika and Amla was 11.1%, 52.4%, and 68.5%, respectively than untreated. Hence, results concluded a significant growth in callus weight after Biofield Energy Treatment, which suggested the action as complementary and alternate approach in order to produce most high-value phytoconstituents from plant callus that can be used for making various drugs, food flavoring and colouring agents.
Keywords: Consciousness Energy Healing